Antiviral Activity of 7-Substituted 7-Deazapurine Ribonucleosides, Monophosphate Prodrugs, and Triphoshates against Emerging RNA Viruses - Milisavljevic, Nemanja; Konkolová, Eva; Kozák, Jaroslav; Hodek, Jan; Veselovská, Lucia; Sýkorová, Veronika; Čížek, Karel; Pohl, Radek; Eyer, Luděk; Svoboda, Pavel; Růžek, Daniel; Weber, Jan; et al. (ACS infectious diseases, 2021)
A series of 7-deazaadenine ribonucleosides bearing alkyl, alkenyl, alkynyl, aryl, or hetaryl groups at position 7 as well as their 5'-O-triphosphates and two types of monophosphate prodrugs (phosphoramidates and S-acylthioethanol esters) were prepared and tested for antiviral activity against selected RNA viruses (Dengue, Zika, tick-borne encephalitis, West Nile, and SARS-CoV-2). The modified triphosphates inhibited the viral RNA-dependent RNA polymerases at micromolar concentrations through the incorporation of the modified nucleotide and stopping a further extension of the RNA chain. 7-Deazaadenosine nucleosides bearing ethynyl or small hetaryl groups at position 7 showed (sub)micromolar antiviral activities but significant cytotoxicity, whereas the nucleosides bearing bulkier heterocycles were still active but less toxic. Unexpectedly, the monophosphate prodrugs were similarly or less active than the corresponding nucleosides in the in vitro antiviral assays, although the bis(S-acylthioethanol) prodrug 14h was transported to the Huh7 cells and efficiently released the nucleoside monophosphate.
Keywords: Purines; ribonukleosidy; RNA-dependentní RNA-polymerasa; Zika Virus; RNA viruses; West Nile virus; 7-deazapurine ribonucleosides; Cell Line, Tumor; Purine Nucleosides; antivirové látky; antiviral activity; COVID-19 Drug Treatment; purinové nukleosidy; Encephalitis Viruses, Tick-Borne; puriny; Prodrugs; farmakoterapie COVID-19; SARS-CoV-2; virus dengue; monophosphate prodrugs; RNA Viruses; Antiviral Agents; RNA-Dependent RNA Polymerase; lidé; Phosphates; Ribonucleosides; prekurzory léčiv; Humans; fosfáty; virus západního Nilu; triphoshates; RNA-viry; viry klíšťové encefalitidy; nádorové buněčné linie; virus zika; Dengue Virus; COVID-19